2004
DOI: 10.1128/ec.3.3.589-597.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Deletion of the Succinate Dehydrogenase Gene KlSDH1 in Kluyveromyces lactis Does Not Lead to Respiratory Deficiency

Abstract: We have isolated a Kluyveromyces lactis mutant unable to grow on all respiratory carbon sources with the exception of lactate. Functional complementation of this mutant led to the isolation of KlSDH1, the gene encoding the flavoprotein subunit of the succinate dehydrogenase (SDH) complex, which is essential for the aerobic utilization of carbon sources. Despite the high sequence conservation of the SDH genes in Saccharomyces cerevisiae and K. lactis, they do not have the same relevance in the metabolism of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 65 publications
1
24
0
Order By: Relevance
“…8A). We have previously shown that K. lactis Klsdh1⌬ mutants devoid of succinate dehydrogenase activity were still able to grow in lactate (31). The requirement of G6PDH for growth on lactate is also supported by the observation that the capability of Klsdh1⌬ mutants to grow on this substrate (31) was lost in Klzwf1⌬ Klsdh1⌬ double mutants (not shown).…”
Section: Vol 6 2007supporting
confidence: 57%
See 2 more Smart Citations
“…8A). We have previously shown that K. lactis Klsdh1⌬ mutants devoid of succinate dehydrogenase activity were still able to grow in lactate (31). The requirement of G6PDH for growth on lactate is also supported by the observation that the capability of Klsdh1⌬ mutants to grow on this substrate (31) was lost in Klzwf1⌬ Klsdh1⌬ double mutants (not shown).…”
Section: Vol 6 2007supporting
confidence: 57%
“…The following K. lactis strains were used in this work: MW179-1D (MAT␣ metA1 ade leu2 trip ura3) (31), CBS2359/3 (MATa hisA1) (provided by M. Wésolowsky), GG1996 (MATa rag2::LoxP) (34), and MS16-21B (MATa metA1 ade leu2 Klsdh1::kanMX4URA3 (this work).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A, lanes 6 and 10). Since Klcox14⌬, differently from Klsdh1⌬ (32), is a respiratorydeficient mutant (11) and Klndi1⌬ is devoid of the major NADH reoxidation activity (35), one can conclude that the expression of the second G6PDH band in the presence of ethanol requires respiration and efficient coenzyme reoxidation.…”
Section: Fig 2 G6pdh Activities Separated On Native Gels For Wild-typmentioning
confidence: 99%
“…1). The Klsdh1⌬ and Klcox14⌬ mutants are unable to assemble complex II and IV (11,32), respectively. Both parental and mutant strains showed a single band of G6PDH activity when grown in glucose ( Fig.…”
Section: Analysis Of G6pdh In Respiratory and Fermentative Mutantsmentioning
confidence: 99%